Manufacturing shop floor problem solving - Norshakinah Binti Saad (School of Materials Engineering, University Malaysia Perlis, 2010)
Quality Control (QC) are scientific management tools, which are uncomplicated used and easy to understand. It forms the fundamental foundation for all problem solving and quality control activities. The most important of this study is to identify the problem in detail and classify root cause that most effect in manufacturing shop floor. Based on the problem study had design and develops a workable solution with implement the specific suggestion to solve the problem at production line. Asian Composites Manufacturing Sdn. Bhd is specializing in manufacturing advanced composite component for aerospace application. As a manufacturing industry have a problem occur that related with products manufacture especially in trimming process by Waterjet machine. The defect occur included delamination and void, fiber breakout or exposed damaged, periphery undersize/oversize, drill holes oversize, Surface roughness, wrong Waterjet program was used, drilled holed shifted , and excess (wrong/undersize/oversize). Based on problem faces this studies have focus on defect of periphery undersize, periphery oversize, delamination and voids to achieve the objective of study. QC Tools were used such as ishikawa diagram, pareto chart, histogram, bar chart and others to identify the root causes and monitoring result after implementation of Preventive Maintenance (PM), Corrective Maintenance (CM) and Total Preventive Maintenance (TPM) as a solution. From these studies has to allow more focus on problem statement study, interpreting the results, develop the specific solution to solve the problem and implement action plans for the improvement of quality. At the end of project, part trim defect at Waterjet machine have been reduced.